HUBUNGAN SIKAP KELUARGA TERHADAP PENYAKIT KRONIS DENGAN KEPATUHAN MINUM OBAT PASIEN PROLANIS - Ratih Ayuningtiyas; Risnandar Risnandar; Yogi Misbahun Nur; Evy Eryta (LPPM Universitas Abdurrab, 2023)
ABSTRACT Hypertension and diabetes mellitus (DM) are chronic diseases with many complications. Discipline or patient compliance with medication is influenced by a variety of factors, one of which is social factors in the form of family attitudes. A positive family attitude is required during the disease treatment process to keep the patient's level of adherence to medication. This study aims to determine the relationship between family attitudes toward chronic disease and medication adherence in Prolanis patients. An observational analytic study design with a cross-sectional study design was used in this study. The purposive sampling technique was used with a total sample of 46 respondents. This study was conducted in 2021 at the Simpang Tiga Health Center in Pekanbaru City. With a p-value of 0.238, this study found no relationship between family attitudes about chronic diseases and medication adherence in Prolanis patients at the Simpang Tiga Health Center in Pekanbaru City. Therefore, patients' families' attitudes about a chronic illness do not have any bearing on how well prolanis patients adhere to their medication.